Etiology, incidence and mortality in patients with ventilator-associated pneumonia in adult general surgery and cardiac surgery intensive care units in University Hospital Dubrava : Etiologija, incidencija i smrtnost u bolesnika s pneumonijom povezanom s mehaničkom ventilacijom u jedinicama intenzivnog liječenja opće i kardijalne kirurgije u Kliničkoj bolnici Dubrava - Karin, Andrea (Array, 2020)
Ventilator-associated pneumonia (VAP) and hospital acquired pneumonia (HAP) strongly contribute to morbidity and mortality in intensive care units. Hospital acquired pneumonia (HAP) is pneumonia occurring 48 hours upon admission and appears not to be incubating at the time of admission. Ventilator-associated pneumonia (VAP) is a type of HAP developing in intubated patients after more than 48 hours upon mechanical ventilation. HAP and VAP are common and serious complications present in hospitalized patients. Since the diagnosis of VAP and HAP are rarely documented, we wanted to assess the incidence of VAP in General Surgery and Cardiac Surgery Intensive Care Units in 2018 and analyse the patients and procedures related factors. Patients intubated and ventilated more than 96 hours during 2018 were included. Our findings have shown that incidence of VAP in two analysed ICUs in UH Dubrava is in line with VAP incidence found in literature due to successful preventive strategies and timely initiation of antimicrobial therapy and other adjunctive procedures.